Phylogeny and evolution of habitat preference in Goniurosaurus (Squamata: Eublepharidae) and their correlation with karst and granite-stream-adapted ecomorphologies in species groups from Vietnam - L. Lee Grismer; Hai Ngoc Ngo; Shuo Qi; Ying-Yong Wang; Minh Duc Le; Thomas Ziegler (Vertebrate Zoology, 2021)
Abstract Maximum likelihood (ML) and Bayesian inference (BI) analyses using two mitochondrial (16S and cyt b) and two nuclear (CMOS and RAG1) genes and 103 specimens recovered the first phylogenies of all 23 extant species of Goniurosaurus. The analyses strongly supported the recognition of four monophyletic species groups with identical inter-specific relationships within the kuroiwae, lichtenfelderi, and yingdeensis groups but discordant topologies at some nodes within the luii group. Both analyses recovered a polyphyletic G. luii with respect to G. kadoorieorum, and owing to the lack of diagnostic characters in the latter, it is considered a junior synonym of G. luii. A stochastic character mapping analysis of karst versus non-karst habitat preference suggested that karstic landscapes may have played a major role in the evolution and diversification of Goniurosaurus. A karst habitat preference is marginally supported as the most probable ancestral condition for Goniurosaurus as well as for the kuroiwae, luii, and yingdeensis groups. However, a non-karst habitat preference is marginally supported as the most probable ancestral condition for the lichtenfelderi group. Multivariate and univariate ecomorphological analyses of the karst-adapted G. catbaensis, G. huuliensis, and G. luii of the luii group and the granite-stream-adapted G. lichtenfelderii of the lichtenfelderi group demonstrated that their markedly statistically different body shapes may be an adaptive response that contributes to habitat partitioning in areas of northern Vietnam where they are nearly sympatric.